2022
DOI: 10.2991/assehr.k.220301.096
|View full text |Cite
|
Sign up to set email alerts
|

The Essentiality of Corporate Reputation on Firm Performance

Abstract: Corporate reputation becomes more important for the investor to make the decision. Reputations reflect to the company's image from the perception and the information from the annual report. The study aims to examine the relationship of corporate reputation on firm performance. Bond rating is one proxy of corporate reputation. Company performance proxied by Tobin's Q and Return on Asset (ROA). This research use sample population from 396 observations on listed companies in the Indonesian Stock Exchange. The dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The findings revealed that throughout the COVID-19 period, the listed firms in 16 countries performed very well. Azizah and Wulaningrum (2022) found in their study that although the COVID-19 pandemic has affected both corporate governance and financial performance, the board of directors and audit committee as corporate governance measures had no significant impact on financial performance during the pandemic. In another attempt, Boshnak et al (2023) tried to analyse the impact of the COVID-19 pandemic on the corporate governance structure of Saudi Arabia-based companies and found that audit committee meetings and audit committee independence were significantly affected by the spread of COVID-19.…”
Section: Corporate Governance and Firm Performance During Covid-19mentioning
confidence: 90%
“…The findings revealed that throughout the COVID-19 period, the listed firms in 16 countries performed very well. Azizah and Wulaningrum (2022) found in their study that although the COVID-19 pandemic has affected both corporate governance and financial performance, the board of directors and audit committee as corporate governance measures had no significant impact on financial performance during the pandemic. In another attempt, Boshnak et al (2023) tried to analyse the impact of the COVID-19 pandemic on the corporate governance structure of Saudi Arabia-based companies and found that audit committee meetings and audit committee independence were significantly affected by the spread of COVID-19.…”
Section: Corporate Governance and Firm Performance During Covid-19mentioning
confidence: 90%